Designing solutions for your business problems : - Vandenbosch, Betty (Jossey-Bass, 2003)
Book is an essential resource for managers and consultants who help organizations resolve ambiguous problems and develop new opportunities. Book will teach you how to curtail investigation and generate and justify ideas without sacrificing thoroughness, creativity, persuasiveness, and fit. You will be able to capitalize on more opportunities, and your problem-solving skills will become more efficient and your solutions more compelling. This work will help you design better solutions and design them faster